Comparação entre as técnicas pré-tarsal e pré-septal na aplicação de toxina botulínica em blefaroespasmo e espasmo hemifacial - Daniel Resende Carvalho Sacramento (2018)
Botulinum toxin has a well-reported efficacy in the treatment of blepharospasm and hemifacial spasm, portraying B and C level of recommendation, respectively. In spite of this clear benefit, only a few studies compared the many injection techniques available in the literature and different protocols lack proper supporting scientific evidence. The present study was then designed to longitudinally compare the pretarsal and preseptal techniques of one hundred and ten patients with blepharospasm and hemifacial spasm. Analysis of seven different scales showed no difference between these techniques neither on maximal effect nor on side effects profiles. However, a significantly longer therapeutic effect duration of the pretarsal was found and a subjective inquiry reported by the patients indicated a preference for the same one. Our data are in agreement with previous studies that suggested that the pretarsal technique may be a better therapeutic option